Acute hip abduction fatigue on lumbopelvic-hip complex stability in softball players - Washington, J.; Gilmer, G.; Oliver, G. (International Journal of Sports Medicine, 2018)
During an overhead throw, the gluteal muscle group stabilizes the lumbopelvic-hip complex (LPHC), leading to efficient energy transfer from the lower to upper extremity. It has been shown that LPHC instability can lead to throwing pathomechanics. The single leg squat has become a common assessment for LPHC stability, and could be used to determine the effects of fatigue on throwing athletes. The purpose of this study was to determine the effects of an acute abduction fatigue protocol on the LPHC of collegiate softball players via the single leg squat assessment of the leg ipsilateral to the throwing arm. Eighteen National Collegiate Athletic Association Division I softball players volunteered (20.5±1.9 years; 169.4±10.0 cm; 72.9±11.5 kg). Each participant performed a single leg squat on the leg ipsilateral to the throwing arm prior to and post side-lying hip abduction fatigue. LPHC and lower extremity kinematics were examined to determine potential effects of fatigue on LPHC stability. There were no significant main effects or interactions of LPHC or lower extremity kinematics during the single leg squat assessments across the fatigue protocol. Based on the current study, an acute bout of fatigue to the hip abductors does not affect LPHC stability in single leg squat execution.